Pengembangan Potensi Desa Wisata Pasirnanjung Geulis - Ayu Latifah; Tedi Supriadi; Gilang Pratama Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The management of Pasirnanjung Geulis tourism village has not been optimal, such as the lack of attractions, lack of visitor management and ticket management. The purpose of this research is to discover the description and potential of Pasirnanjung Geulis Tourism Village, as well as the steps that have been taken or are needed to develop it. This research uses a qualitative method with a case study design. This research was taken in three stages using data triangulation, namely interviews, observation, and documentation research, and there were ten participants or sources used to analyze the data. To analyze the data, this research collects data, presents data, reduces data using NVivo, and draws conclusions. Pasirnanjung Geulis Tourism Village has great potential as a tourist destination because of its natural beauty and cultural wealth. However, the development of tour packages, ticketing systems, social media management, and the provision of basic facilities are all still needed. The village has yet to generate equitable financial benefits for the entire local population, despite many people contributing.